A study on magnetic curves in trans-Sasakian manifolds - Bozdağ Şerife Nur (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2023)
In this paper, we focused on biharmonic, f-harmonic and f-biharmonic magnetic curves in trans-Sasakian manifolds. Moreover, we obtain necessary and su cient conditions for magnetic curves as well as Legendre magnetic curves to be biharmonic, f-harmonic and f-biharmonic. We investigate the states of these conditions in α-Sasakian, β-Kenmotsu and cosymplectic manifolds. Besides, we obtain some nonexistence theorems.